The first radiolabeled 68Ga-FAPI-46 for clinical PET applications using a fully automated iQS-TS synthesis system in Thailand - Boonkawin, Natphimol; Chotipanich, Chanisa (The Journal of Chulabhorn Royal Academy, 2021)
Background: Gallium-68 labeling of various peptides is now widely used in routine clinical positron emission tomography (PET) applications. We used an automated synthesis system at the National Cyclotron and PET Center of Chulabhorn Hospital to reduce human errors, lower the radiation dosages to operators during synthesis, and establish high product yields. Methods: In this study, we synthesized 68Ga-labeled FAPI-46 peptide using the fully automated iQS-TS theranostics module. The radiosynthesis of 68Ga-Fapi-46 was completed in 15 min, including generator elution and dispensing radiopharmaceuticals. Results: The 68Ga-FAPI-46 radiosynthesis yielded product with 70% ± 2% activity and >95% radiochemical purity. All quality control parameters conformed with the limits prescribed by the European Pharmacopoeia. Conclusion: This study demonstrated successful synthesis of 68Ga-labeled FAPI-46 peptide using the fully automated iQS-TS theranostics module, which produced reliable and reproducible synthetic yields. The 68Ga-FAPI-46 product is of high purity that exceeds minimum recommended requirements.